Higher Education of India for Management: Challenges and Opportunities (International Journal of Food and Nutritional Sciences, 2022)
Globally, management education is currently being plagued by a specific issue of relevance. The calibre of MBA aspirants, the curriculum, business research, the calibre of research publications, industry-institute interface, management development programmes, faculty development programmes, placements, compensation for business school graduates, alumni career development pathways, faculty and student diversity, governance and accountability, etc., are all being closely scrutinised. This essay looks at the situation of management education in India today following the American financial crisis and the Satyam case. This essay also examines management education trends in India and seeks to understand how management education affects people and businesses there. Additionally, it explores current difficulties in management education and provides suggestions for norms and directives to advance management education in India. Due to a lack of study in this field, this publication will fill a gap in the literature.Green marketing, which influences the standard marketing mix (manufactured goods, price, promotion, and site) as well as the process of determining community policy, is undoubtedly important to overall business strategy. As a result, green promotion covers a wide spectrum of behaviours. Examining the evolution of green marketing and the green initiatives put out by various businesses is the main objective of this essay. Take note of the challenges Green Marketing encounters as well.